Pediatric Obstructive Sleep Apnea: Consensus, Controversy, and Craniofacial Considerations. Issue 5 (November 2017) - Garg, Ravi K.; Afifi, Ahmed M.; Garland, Catharine B.; Sanchez, Ruston; Mount, Delora L.
Abstract : Summary: Pediatric obstructive sleep apnea, characterized by partial or complete obstruction of the upper airway during sleep, is associated with multiple adverse neurodevelopmental and cardiometabolic consequences. It is common in healthy children and occurs with a higher incidence among infants and children with craniofacial anomalies. Although soft-tissue hypertrophy is the most common cause, interplay between soft tissue and bone structure in children with craniofacial differences may also contribute to upper airway obstruction. Snoring and work of breathing are poor predictors of obstructive sleep apnea, and the gold standard for diagnosis is overnight polysomnography. Most healthy children respond favorably to adenotonsillectomy as first-line treatment, but 20 percent of children have obstructive sleep apnea refractory to adenotonsillectomy and may benefit from positive airway pressure, medical therapy, orthodontics, craniofacial surgery, or combined interventions. For children with impairment of facial skeletal growth or craniofacial anomalies, rapid maxillary expansion, midface distraction, and mandibular distraction have all been demonstrated to have therapeutic value and may significantly improve a child's respiratory status. This Special Topic article reviews current theories regarding the underlying pathophysiology of pediatric sleep apnea, summarizes standards for diagnosis and management, and discusses treatments in need of further investigation, including orthodontic and craniofacial interventions. To provide an overview of the spectrum of disease and treatment options available, a deliberately broad approach is taken that incorporates data for both healthy children and children with craniofacial anomalies.